Dynamic Response of Low-Aspect-Ratio Cantilever NACA0012 Airfoil at Low-To-Moderate Reynolds Numbers - García-González, Antonio Luis; Martínez-Aranda, Sergio; Velázquez-Navarro, José Francisco; Parras-Anguita, Luis; Del-Pino-Peñas, Carlos Manuel (Springer, 2018)
The influence of the angle of attack (AoA) and the chord based Reynolds number (Rec) on the lift and drag coefficients has been analyzed experimentally in a low-aspect-ratio NACA0012 airfoil, AR 2. Results are shown for chord based Reynolds numbers in the range 3.33×104 ≤Rec ≤1.33×105 and AoA between 0º and +35º, the stall angle being close to 12º. The aerodynamic characteristics show an increase and decrease of lift and drag force fluctuations for AoA greater than the stall angle. The explanation of how these aerodynamic variations appear has been reported numerically and it is based on two-dimensional effects which are mainly the unstable laminar separation bubble (LSB) and the subsequent downstream propagation of leading edge vortex (LEV) as AoA increases. In addition, the dynamic response of the wing has been studied using frequency analysis. We compute the power spectral density (PSD) from the temporal evolution of the net force exerted over the wing, showing that the main response of the wing is the presence of two natural frequencies of the wing-base system. The mean PSDsuddenly increases for Rec ≈1×105, particularly at AoA exceeding the critical point that corresponds to the stall angle. Finally, and despite from the fact that our model is rigid, we find PSD peaks at very low and high frequencies in agreement with other authors’ results which correspond to energetic modes in the wingtip vortex and the formation and emission of coherent turbulent structures behind the airfoil, respectively.
Keywords: Aerodinámica; Finite wing; Low re aerodynamics; Dynamic response; Wingtip vortex